2022
DOI: 10.53379/cjcd.2022.330
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sport-Life Balance and Well-Being on Athletic Performance

Abstract: The present study explores the role of sport-life balance and well-being on athletic performance. Canadian athletes who competed at the 2019 Pan American and Para Pan American Games in Lima, Peru were invited to participate in the survey via email. A mixed-methods design was utilized, consisting of an online survey and semi-structured, follow-up interviews. The sample consisted of 72 athletes, spanning eighteen different sports. Our findings demonstrate that while many Olympic and Paralympic athletes are succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
“…Recent studies have looked at the social support provided by the best friend and its influence on adolescent’s practical physical activity and perceived benefits ( Martin and Smith, 2002 ; Martin, 2006 ; Stearns et al, 2018 ; Kandola et al, 2020 ; Monteiro et al, 2021 ). On the other hand, in sports for people with disabilities context, social support is also considered to be a positive influence ( Swanson et al, 2008 ; Machida et al, 2013 ; Crawford et al, 2015 ; Fiorilli et al, 2016 ; Haslett et al, 2017 ; Powell and Myers, 2017 ; Cardoso et al, 2018 ; Atkinson and Martin, 2020 ; Aitchison et al, 2021 ; Mira et al, 2022 ; Monton et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social support and well-being are two important constructs in athletes with disabilities and their relationship has been evidenced in several studies ( Crawford et al, 2015 ; Fiorilli et al, 2016 ; Haslett et al, 2017 ; Atkinson and Martin, 2020 ; Aitchison et al, 2021 ; Mira et al, 2022 ; Monton et al, 2022 ). Waldinger and Schulz (2016) argues that social connections are very important, people who are more socially connected are happier, healthier, and live longer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations